Overcoming stress-induced brain fog : 10 simple ways to find focus, improve memory & feel grounded - Weber, Jill P., 1973- (Tantor Media, Inc., 2022)
Do you ever feel spaced out or stuck in a rut, like you just can't think, or you're moving in slow motion? Perhaps you feel detached or disengaged, defeated and hopeless, or just not fully yourself. If you're struggling with a lack of mental clarity, energy, and belief in yourself and your capabilities, you may be experiencing the dreaded brain fog-a very real issue that can result from the exhaustion, overstimulation, and the stress of modern life. All of us struggle to find the get-up-and-go we need sometimes, but when prolonged stress and anxiety begin to affect your ability to focus, concentrate, remember, solve problems, or communicate effectively on a regular basis, these symptoms may point to something more than just a stressful week. It's time to clear away the fog and reclaim your motivation, passion, self-worth, zest, and meaning in life. Based on cutting-edge research, Overcoming Stress-Induced Brain Fog offers quick solutions you can put to work right away, including exercises based in awareness, mindfulness and acceptance, and self-compassion. With these ten easily accessible tools, you'll find your way out of the haze toward clarity, improved memory, and a greater presence to enjoy life.